2005
DOI: 10.1007/s00296-004-0496-3
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of osteoporosis in patients with rheumatoid arthritis receiving glucocorticoids: a comparison of alendronate and intranasal salmon calcitonin

Abstract: The results of this study demonstrated that alendronate treatment produced significantly greater increases in the femoral neck BMD and greater decreases in bone turnover than intranasal sCT in RA patients receiving low dose glucocorticoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…Eleven trials were classified as treatment trials because BPs was given for long-term GC user. Of these 11 treatment trials, the mean dosage of GC consumption was greater than 7.5 mg/day (prednisone equivalent) in 6 trials [19], [38], [46]–[49], less than 7.5 mg/day in 5 trials [20], [21], [39], [40], [43]. No GC usage in 1 trial [37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven trials were classified as treatment trials because BPs was given for long-term GC user. Of these 11 treatment trials, the mean dosage of GC consumption was greater than 7.5 mg/day (prednisone equivalent) in 6 trials [19], [38], [46]–[49], less than 7.5 mg/day in 5 trials [20], [21], [39], [40], [43]. No GC usage in 1 trial [37].…”
Section: Resultsmentioning
confidence: 99%
“…No GC usage in 1 trial [37]. calcium and vitamin D was given to patients in 10 trials [19], [21], [22], [38][40], [43], [45]–[47], only calcium in 5 trials [34], [36], [41], [42], [49], only placebo in 5 trial [20], [33], [37], [44], [48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane review assessing the efficacy of calcitonin for treatment and prevention of GIOP demonstrated preservation in lumbar BMD at 12 months, but not at 24 months compared to placebo [73]. One study found that alendronate was significantly better than intranasal calcitonin at increasing BMD and decreasing bone turnover [74]. There is also a concern for increased risk of malignancy such as basal cell carcinoma and prostate cancer, although the data is not strong for a causal relationship [75].…”
Section: And Calcitoninmentioning
confidence: 91%
“…Eine Steigerung der Knochendichte bei GIO konnte auch bei der Anwendung von Calcitonin beobachtet werden [2]. Jedoch fallen die Effekte im Vergleich zu den Bisphosphonaten geringer aus [21].…”
Section: Weitere Möglichkeiten Der Therapieunclassified